MENJADI PINTAR DENGAN TEMATIK: PENDEKATAN BARU DALAM BELAJAR UNTUK KELAS III SEKOLAH DASAR STUDI DI MADRASAH IBTIDAIYAH 2 NW TALUN LOMBOK TIMUR - Huda, Nurul; Hadi, Hairul (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
This study proposes a new approach to learning for third-grade students at Madrasah Ibtidaiyah NW Talun, East Lombok. The main objective is to enhance students' intelligence levels through the development of innovative teaching methods. The research combines a thematic approach with information technology to create a more interactive and engaging learning experience. Involving teachers, students, and technology, this method is designed to enrich conceptual understanding and stimulate the creativity and curiosity of students. The research results demonstrate a significant improvement in academic achievement and student engagement, fostering a more dynamic and collaborative learning environment. These findings contribute to the development of a more adaptive and relevant curriculum, providing practical insights for educators and educational institutions seeking to enhance the quality of elementary-level learning.